Economic reintegration postreturn—examining the role of return voluntariness, resource mobilization and time to prepare. Issue 7 (6th June 2022) - Monti, Andrea; Serrano, Inmaculada
Abstract: This paper examines conditions of international return migration and their relation to risks of experiencing economic difficulties postreturn. Relying on unique survey data among Senegalese and Romanian returnees, we revisit and provide an empirical examination of the theoretical notion of return preparedness, involving aspects of voluntariness, resource mobilization and time to prepare. The lack of time to prepare return, more commonly associated with self‐declared involuntary returns and deportations, is found to significantly increase the risk of economic difficulties post return in both contexts. Whilst emphasizing the complexity of voluntariness, the findings show that, additionally, returns compelled by external circumstances or negative return motivations ('semi‐involuntary') are associated with higher risks of economic difficulties. Compared to nonmigrants, returnees experienced decreased risks of economic difficulties in Senegal, but not significantly in Romania. Those forced back to Senegal or compelled to return to Romania did, however not experience such risk decrease.